IMPLIKASI HUKUM PIDANA TERHADAP PENJEMPUTAN PAKSA JENAZAH PASIEN OLEH PENGEMUDI ONLINE DI R.S.U.P M.DJAMIL PADANG - Yandriza, Yandriza; Elvandari, Siska (Universitas Ekasakti, 2023)
Law Number 44 of 2009 states that: a hospital is a health service institution that provides comprehensive individual health services that provide inpatient, outpatient and emergency services. This latest development increasingly shows that the hospital has de facto shifted from a social institution to a business institution. In efforts to provide health services that aim to dignify patients as whole human beings at this time it often occurs because of imperfect laws which often cannot reach reality. It can be seen that several cases were found in various hospitals, due to the economic limitations of the patient. Thus resulting in the patient being unable to complete hospital administration after the patient was declared dead, and this suddenly went viral on various social media, because these online drivers did not come to visit their sick colleagues or to carry out demonstrations, but forced the bodies of children from one of his fellow online drivers who died, who was allegedly made difficult by the hospital, due to economic limitations in the patient's (victim's) family was unable to complete hospital administration.